Rancang Bangun Aplikasi Absensi Pada Guru Dengan Menggunakan Qr Code Berbasis Website (Studi Kasus: Sd Pasir Awi) - Malthufah, Yayu; Sujana, Dadang (Universitas Islam Syekh Yusuf, 2022)
Technological developments are growing rapidly so that they can influence and facilitate humans in the field of telecommunications and digitalization. More and more people are taking advantage of the ease of using the internet in this digital era. One of the technological developments that occur is by developing attendance especially in the school environment, attendance which was originally manual can be developed to be more efficient and easy by using a website that is connected to the internet. Attendance is one of the important things in human life, especially in the field of Education. Attendance reports are important for teachers in terms of teaching in schools, attendance reports are considered important because they can be an example of how to see someone's discipline in the agency. The attendance system for teachers in schools is one example.